2003
DOI: 10.1007/bf03166621
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-model analysis of effective CIDEP distance in solvent-separated radical-ion pair

Abstract: The radical pair mechanism (RPM) of chemically induced dynamic electron polarization (CIDEP) is theoretically analyzed to determine what intermolecular separations (reŸ effectively cont¡ to the CIDEP generated from diflhsive, separated radical-ion pairs (RIP) in terms of the chargetransfer interaction in the singlet-triplet energy splitting (J) by taking into aceount the distance-dependent electronic coupling and reorganization energy. The diffusion-model analysis reveals that the hyperŸ237 RPM polarization (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Concerning solvent-separated radical ion pairs (RIP) produced via intermolecular, photoinduced charge separation (CS) reactions, the energy gap (2 J = E S − E T ) between the singlet (S) and triplet (T 0 ) states has been shown to be dominated by charge-transfer interactions ( J CT ); J CT is determined by V DA via the charge-recombination configurations in accordance with the Marcus theory. , Since the β determines the distance dependence of 2 J , , the β strongly influences chemically induced dynamic electron polarization (CIDEP) created through the spin interactions within transient RIPs. During diffusional motion on the S and T 0 potential surfaces, radical pair mechanism (RPM) electron spin polarization is created on ion radicals due to the S−T 0 state mixing taking place around the center-to-center intermolecular distance of 12 Å (in the case of β = 1 Å -1 ), where the magnitude of 2 J is comparable to that of the hyperfine coupling (typically ca. 10 8 rad/s).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning solvent-separated radical ion pairs (RIP) produced via intermolecular, photoinduced charge separation (CS) reactions, the energy gap (2 J = E S − E T ) between the singlet (S) and triplet (T 0 ) states has been shown to be dominated by charge-transfer interactions ( J CT ); J CT is determined by V DA via the charge-recombination configurations in accordance with the Marcus theory. , Since the β determines the distance dependence of 2 J , , the β strongly influences chemically induced dynamic electron polarization (CIDEP) created through the spin interactions within transient RIPs. During diffusional motion on the S and T 0 potential surfaces, radical pair mechanism (RPM) electron spin polarization is created on ion radicals due to the S−T 0 state mixing taking place around the center-to-center intermolecular distance of 12 Å (in the case of β = 1 Å -1 ), where the magnitude of 2 J is comparable to that of the hyperfine coupling (typically ca. 10 8 rad/s).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed a novel method to investigate the λ for photoinduced ET systems using time-resolved EPR (TREPR) spectroscopy in polar solvents. ,, In our previous papers, the λ values for the charge recombination reactions were determined with the good accuracy from the observation of the chemically induced dynamic electron polarization (CIDEP) generated in nanometer-separated radical ion pairs (RIPs). It was found that the solvent reorganization energies are larger by ca.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kobori et al [15,16] showed that the distance dependence of the JcT value is affected by the exponential decay constant q of the squares of electronic coupling matrix elements in SSRIPs. The effective polarization distance of 1.2 nm can be applied under the condition of ti= 10 nm -1 [19,26]. Since the effective polarization distance dramatically changes with the /3 value [26], the large deviation of more than 0.1 eV may be due to a deviation of the distante of 1.2 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The effective polarization distance of 1.2 nm can be applied under the condition of ti= 10 nm -1 [19,26]. Since the effective polarization distance dramatically changes with the /3 value [26], the large deviation of more than 0.1 eV may be due to a deviation of the distante of 1.2 nm. According to the solvent-mediated superexchange model [29,30], the distance dependence of the electronic coupling is predicted to be affected by the redox properties of solvent and solute molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation